Access to and Socio-economic Impact Assessment of Computer/Internet in Rural Haryana, India (Indian Journal of Extension Education, 2013)
The study was conducted on a sample of 200 respondents comprising of 100 males and 100 females drawn from four villages of Hisar district. The data were collected on structured interview schedule regarding personal life of rural respondents it was found that computer/internet had moderate impact in terms of entertainment, enhancement of skill and current news in case of male respondents, while for female respondents, moderate impact was observed in areas of quality of education, enhancement of skill, and selection of reading material. Data of social impact of rural clientele clearly indicated that majority of male respondents had moderate impact in terms of social status, social relationship and social awareness whereas, moderate impact was observed in life of female respondents in areas of social status, social awareness and social networking. Computer/internet had moderate impact in education in terms of awareness about admission, career information, job opportunities on the life of male and female respondents, while it had moderate impact in area of internet banking and financial management as far as economic aspect is concerned. Computer / internet had moderate impact on life of male respondents in terms of preventing crop disease, live stock keeping and preventing animal disease whereas, it had low impact in the areas of preventing animal diseases, preventing crop diseases and livestock keeping. Association of socio-economic variables of male and female respondents indicate significant association of age, education and occupation with access to computer/internet whereas, significant association of age and education was found with control of computer/internet. Significant association of complete access with impact of computer/internet was found where as complete control on use and selling and purchase of computer/internet was significantly associated with impact of computer/internet on rural clientele. Main constraints in use of computer/internet were economic dependency, lack of decision making ability, lack of control on use of computer/internet and lack of power supply.